2016
DOI: 10.1080/17482798.2016.1233893
|View full text |Cite
|
Sign up to set email alerts
|

“People think it’s a harmless joke”: young people’s understanding of the impact of technology, digital vulnerability and cyberbullying in the United Kingdom

Abstract: Young people's technology use has increased exponentially over the last few years. To gain a deeper understanding of young peoples' experiences of digital technology and cyberbullying, four focus groups were conducted with 29 11- to 15-year-olds recruited from two schools. Interpretative phenomenological analysis revealed three themes: impact of technology, vulnerability and cyberbullying. Technology was seen as a facilitator and a mechanism for maintaining social interactions. However, participants reported e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
111
0
88

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(200 citation statements)
references
References 54 publications
1
111
0
88
Order By: Relevance
“…The growing use of a wide variety of technologies has created new forms of possible interaction and communication among adolescents (Betts and Spenser 2017;Goodyear and Armour 2018). Information and communication technologies (ICTs) provide many advantages for young people.…”
Section: Introductionmentioning
confidence: 99%
“…The growing use of a wide variety of technologies has created new forms of possible interaction and communication among adolescents (Betts and Spenser 2017;Goodyear and Armour 2018). Information and communication technologies (ICTs) provide many advantages for young people.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the current research has demonstrated the presence of an optimistic bias for the relative risk of experiencing cyber bullying and offers an exploration for why individuals believe they will not experience cyber bullying (Betts and Spenser 2017). The research also highlights variations according to comparator groups, age, and gender.…”
Section: Discussionmentioning
confidence: 60%
“…However, this finding may also reflect (a) that females are more likely to experience cyber bullying than males (Dehue et al 2008) and (b) the proportion of females in the current sample. The current findings suggest that comparative optimism is the mechanism underpinning Betts and Spenser's (2017) finding that young people believe that they are not at risk of cyber bullying. Participants may be holding self-serving biases about the risk of cyber bullying to maintain their self-esteem (Metzger et al 2015), although future research should directly explore this line of enquiry.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations